Dry anaerobic digestion of organic waste: a review of operational parameters and their impact on process performance - Rocamora, Ildefonso; Wagland, Stuart T.; Villa, Raffaella; Simpson, Edmon W.; Fernández, Oliver; Bajón Fernández, Yadira (Elsevier, 2019)
Dry digestion is a suitable technology for treating organic wastes with varying composition such as the organic fraction of municipal solids waste. Yet, there is a need for further research to overcome some of the disadvantages associated with the high total solids content of the process. Optimisation of inoculum to substrate ratio, feedstock composition and size, liquid recirculation, bed compaction and use of bulking agents are some of the parameters that need further investigation in batch dry anaerobic digestion, to limit localised inhibition effects and avoid process instability. In addition, further attention on the relation between feedstock composition, organic loading rate and mixing regimes is required for continuous dry anaerobic digestion systems. This paper highlights all the areas where knowledge is scarce and value can be added to increase dry anaerobic digestion performance and expansion.
Keywords: Dry Anaerobic digestion; Operational parameters; Organic fraction of the municipal solid waste; percolate recirculation